2002
DOI: 10.14411/fp.2002.035
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood vessels and lungs in the dissemination of Naegleria fowleri following intranasal inoculation in mice

Abstract: Abstract. Primary amoebic meningoencephalitis (PAM) was induced in mice by intranasal inoculation of Naegleria fowleri (Singh et Das, 1970) to study the role of the blood vessels and lungs in the early and later stages in this disease. Upon culturing blood and lung tissue obtained at 24-, 36-, 48-, 72-, 96-, and 120-hour time periods, it was found that amoebae grew only from blood and lung tissue obtained at the 96 and 120 hour time periods. Paraffin sections of the head revealed small foci of acute inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…These results confirmed previous experiments with BSM and PSM, and showed that the mucin MUC5AC may be an important protective barrier, reducing adhesion and cytotoxicity to the airway epithelium. Histopathological studies using a murine model have shown that this amoeba infects its host by invading the olfactory mucosa, migrating through the olfactory nerves, crossing the cribiform plate, and entering the olfactory bulbs (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002. At the very early stages of infection, trophozoites are observed at the lumen of the nasal cavity embedded in mucus secretions (Rojas-Hernández et al, 2004).…”
Section: Nci-h292 Cells and Muc5ac Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirmed previous experiments with BSM and PSM, and showed that the mucin MUC5AC may be an important protective barrier, reducing adhesion and cytotoxicity to the airway epithelium. Histopathological studies using a murine model have shown that this amoeba infects its host by invading the olfactory mucosa, migrating through the olfactory nerves, crossing the cribiform plate, and entering the olfactory bulbs (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002. At the very early stages of infection, trophozoites are observed at the lumen of the nasal cavity embedded in mucus secretions (Rojas-Hernández et al, 2004).…”
Section: Nci-h292 Cells and Muc5ac Assaysmentioning
confidence: 99%
“…It has been demonstrated that this protozoan gains access to the CNS by penetrating the olfactory neuroepithelium and invading the olfactory bulbs (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002Rojas-Hernández et al, 2004). Once in the CNS, the amoebae induce a strong inflammatory response with lysis of leukocytes that contributes to tissue damage (Cervantes-Sandoval et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…fowleri is the causal agent of PAM, and the acquisition of this entity is commonly associated with a recent history of aquatic activity by the patient (Schuster & Visvesvara, 2004). The route of invasion of N. fowleri has been analysed by histopathological studies using a mouse model (Carter, 1970;Cervantes-Sandoval et al, 2008a;Jaroli et al, 2002). These studies revealed that the amoeba infects the host by first penetrating the olfactory mucosa and subsequently crossing the cribriform plate of the ethmoid bone, eventually reaching the olfactory bulbs of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…PAM is an acute and rapidly fatal infection that is characterized by parasitic invasion of the central nervous system (CNS). The parasite gains access to the CNS by penetrating the olfactory neuroepithelium and migrating through olfactory nerves until it reaches the olfactory bulbs (Carter, 1970;Jaroli et al, 2002;Jarolim et al, 2000;Rojas-Hernández et al, 2004;Shibayama et al, 2003). Immunohistochemical studies of the early events of infection using a murine model have shown that the amoebae induce intense mucus secretion and an inflammatory reaction in the nasal cavity (Cervantes-Sandoval et al, 2008a;Rojas-Hernández et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The infection usually occurs after performing aquatic activities in water bodies containing the parasite (Schuster & Visvesvara, 2004;Marciano-Cabral & Cabral, 2007). Histopathological studies using a mouse model showed that the amoebae infect the host by penetrating the olfactory mucosa, migrating through the olfactory nerves, and passing through the cribriform plate to reach the olfactory bulbs of the CNS, where an intense inflammatory reaction is produced (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002Cervantes-Sandoval et al, 2008a). In the very early stages of infection, trophozoites are seen in the lumen of the nasal cavity embedded in a large amount of mucus and surrounded by infiltrated neutrophils (Thong et al, 1983;Rojas-Hernández et al, 2004;Cervantes-Sandoval et al, 2008b).…”
Section: Discussionmentioning
confidence: 99%